Lessons in ecology and conservation from a tropical forest fragment in Singapore - Lum, Shawn (2022)
Forest fragments are increasingly common in the tropics as pristine forests are cleared. Fragments stranded within cities are especially stress-prone due to their greatly altered environment and high human impacts. We review biodiversity and ecological studies from Bukit Timah, a tropical forest fragment in Singapore, to ask how this forest has contributed to our understanding of tropical ecology and fragmentation effects, and list the conservation values of this forest. Evidence from Amazonian fragments predicts that losses in diversity and forest function follow fragmentation, and although Bukit Timah has adhered to some of those predictions, other aspects of the forest appeared remarkably resilient. As might be expected, declines in plant, invertebrate, bird, and mammal diversity occurred not only historically but also across two surveys made about 20 years apart. In other ways Bukit Timah proved surprising. Aboveground biomass fluctuated but did not plummet drastically, and was comparable to levels found in primary forests in the region. The extirpation of large fauna did not appear to reduce the dispersal of large seeded plant species, likely due to continued dispersal by small-mammals and birds. Exotic tree species are confined to recovering secondary forest fringes and do not threaten the primary forest, except for perhaps shade tolerant Pará rubber and a handful of cultivated fruit trees. Studies of birds and plants found that life history differences could account for differences in genetic connectivity or isolation for different species, with population genetic implications for other taxa. Despite being a small fragment, new species of plants and animals continue to be discovered or re-discovered. Clearly, there are reasons to celebrate Bukit Timah as a forest fragment that withstood two centuries of human impacts. Nonetheless, many measures can be implemented to better secure its future.